Vocabulary and Writing in a First and Second Language - Albrechtsen, D. author. aut Link
XVII, 225 p.
Keywords: Listening to the voices of learners as they write an essay or try to cope with unfamiliar words in a text is a luxury often reserved for researchers. This book observes individuals performing similar tasks in their first and their foreign language and invites readers with an interest in foreign language acquisition to follow the same learners in their efforts to cope in both languages.